The Effectiveness and Student's Perception of an Adaptive Learning System - Reyos Malabanan, Diana (PT FORMOSA CENDEKIA GLOBAL, 2024)
The study aims to examine the impact of an adaptive learning system on students' academic performance and their overall perception of using the system. This study employed a quantitative research design to gather data, ideas, and information. There are 55 participants in the study comprising 33 students for the treatment group (utilizing an adaptive learning system) and 22 students for the control group. The findings showed that the adaptive learning intervention increased student motivation leading to a more positive learning experience and no statistically significant difference exists between the perception of AL experience among academic status and specialization. Students who went through the adaptive learning intervention demonstrated improved academic performance overall. The study presents recommendations for implementing an adaptive learning system effectively, including comprehensive training for teachers and administrators, selecting appropriate platforms, training teachers, and monitoring student progress.